EVALUASI PENGGUNAAN BANTUAN OPERASIONAL SEKOLAH (BOS) DI MADRASAH IBTIDAIYAH SWASTA LEBONG TAMBANG - Adi Suardi; UFN Ifnaldi; UFN Murniyanto; UFN Hamengkubuwono (Oasis : Jurnal Ilmiah Kajian Islam, 2020)
This study aimed to find an overview as regards the evaluation concerning the use of school operational assistance funds (BOS) at MIS 01 Lebong Tambang by using a qualitative approach. The data were obtained using observation and interview techniques. After collected, the data were analyzed using the Miles, Huberman and Saldana’s approach extending to data selection, data presentation, and conclusion drawing. This study concluded that the evaluation of distribution and use of school operational assistance funds (BOS) conducted by the school became a very helpful medium for the school per se. Such evaluation was oriented towards increasing the resources of teaching staffs. Based on evaluation, it was found a mismatch between the budget ceiling of BOS and the teachers’ needs. School facilities and infrastructure such as the construction of new classrooms, let alone Worship facilities such as Musalla, could not use school operational assistance funds (BOS), so it was very difficult for the school because for RKB the budget had to be separated from the school operational assistance funds (BOS).